2011
DOI: 10.2212/spr.2011.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment of grain-processing facilities for insect management: a historical overview and recent advances

Abstract: Purpose of review:Tactics to manage infestations of stored-product insects in grain-processing facilities historically included the use of heat treatments and the fumigant methyl bromide. The phase out of methyl bromide in the USA in 2005, because of its adverse effects on stratospheric ozone, has renewed interest in using heat treatments. In this review, a brief history regarding the use of heat treatments in grain-processing facilities, such as flour mills, is described along with recent research development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This finding deserves additional attention given that it could be used to inform facility managers about the efficacy of different control tactics deployed. For instance, all 3 facilities perform at least 1 heat treatment throughout the year, and it has been reported that T. castaneum was more tolerant than other species such as L. serricorne to heat (Subramanyam et al 2011). Deploying multiple trap types to monitor population levels before and/or after heat treatments and other pest management strategies can provide useful information about why the relative abundance of certain species changes over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding deserves additional attention given that it could be used to inform facility managers about the efficacy of different control tactics deployed. For instance, all 3 facilities perform at least 1 heat treatment throughout the year, and it has been reported that T. castaneum was more tolerant than other species such as L. serricorne to heat (Subramanyam et al 2011). Deploying multiple trap types to monitor population levels before and/or after heat treatments and other pest management strategies can provide useful information about why the relative abundance of certain species changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…This finding deserves additional attention given that it could be used to inform facility managers about the efficacy of different control tactics deployed. For instance, all 3 facilities perform at least 1 heat treatment throughout the year, and it has been reported that T. castaneum was more tolerant than other species such as L. serricorne to heat (Subramanyam et al 2011).…”
Section: Factormentioning
confidence: 99%
“…Overall, the use of heat treatments for stored-product pest control has had a circular history (66,137). Once replaced by methyl bromide fumigation, heat treatments are now replacing methyl bromide, which is being banned as an ozone depleter.…”
Section: Extreme Temperature Treatmentsmentioning
confidence: 99%
“…In sub-Saharan Africa, the storage of grains is unavoidable to maintain a constant supply given the periodic production pattern [6]. Storage of grains in many rural African settings, typical of northern Uganda, comes with an elevated cost of grains contamination with fungi due to inappropriate storage structure [7]. The common grain storage structure comprises; sisal bags, pits, wood and wire cribs, wooden open-air, polythene bags, and heaping on floor [8].…”
Section: Introductionmentioning
confidence: 99%